2017
DOI: 10.1002/em.22069
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of atrazine and 2,4‐D exposure and oxidative stress markers among iowa corn farmers

Abstract: Reactive oxygen species, potentially formed through environmental exposures, can overwhelm an organism’s antioxidant capabilities resulting in oxidative stress. Long-term oxidative stress is linked with chronic diseases. Pesticide exposures have been shown to cause oxidative stress in vivo. We utilized a longitudinal study of corn farmers and non-farming controls in Iowa to examine the impact of exposure to the widely used herbicides atrazine and 2,4-dichlorophenoxyacetic acid (2,4-D) on markers of oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 48 publications
(68 reference statements)
0
16
2
11
Order By: Relevance
“…Here in KS applicators, we observed increased 8-isoprostane (third quartile of 2,4-D exposure), but not in the fourth quartile and no evidence of a monotonic trend. Our findings did not replicate the earlier study, despite evaluating the same urinary oxidative stress markers in applicators with measured urinary levels of 2,4-D much higher than those reported in Iowa corn farmers 13. For example, the lowest quartile of exposure in the KS weed applicators encompassed the entire range of 2,4-D exposures reported in the Iowa corn farmers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Here in KS applicators, we observed increased 8-isoprostane (third quartile of 2,4-D exposure), but not in the fourth quartile and no evidence of a monotonic trend. Our findings did not replicate the earlier study, despite evaluating the same urinary oxidative stress markers in applicators with measured urinary levels of 2,4-D much higher than those reported in Iowa corn farmers 13. For example, the lowest quartile of exposure in the KS weed applicators encompassed the entire range of 2,4-D exposures reported in the Iowa corn farmers.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, the lowest quartile of exposure in the KS weed applicators encompassed the entire range of 2,4-D exposures reported in the Iowa corn farmers. One reason for the difference in the results could be the age difference in the two study populations; the mean age in the Iowa study is 51 years, almost 20 years older than this analysis 13. In the present study, 2,4-D was not measured at baseline for controls or applicators.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Several studies in humans reported an imbalance between oxidative stress markers and the antioxidant defences in farmers/pesticide applicators or agricultural workers (7,(100)(101)(102). However, a thorough search of relevant literature yielded only one epidemiological study of the association between the biomarkers of atrazine exposure and biomarkers of oxidative stress (103), and none about terbuthylazine. In that one study, no association was found between atrazine mercapturate (AM) and MDA, 8-hydroxy-2'-deoxyguanosine (8-OHdG), or 8-isoprostaglandin-F2 (8-isoPGF) in urine samples collected from 30 farmers over five time points of atrazine application.…”
Section: Epidemiological Studiesmentioning
confidence: 99%